An Embodied Existence in Heaven and the Non-Cartesian Substance Dualism - Perez, Alejandro (TheoLogica, 2021)
In this paper, I propose to imagine, through Non-Cartesian substance dualism (NCSD), how we could resurrect. Even though many objections have been addressed to the classic conception of eschatology since the beginning of the century of eschatology, I propose we have some reasons to think that a more corporeal conception of the eschaton is not only desirable but also metaphysically possible and compatible with biblical data. I shall explore what I call the Christ Body Argument, which invites us to reject, on the one hand, a disembodied existence in heaven, and on the other side to adopt a corporeal existence of Christ in heaven. A kind of Dualism, and more precisely, one possessing NCSD’s virtues, could play a role in exploring this new theological option. I expect to show that NCSD is a metaphysical option allowing us to understand better what we are. If we hope and believe in the resurrection of the dead, NCSD provides an interesting model to think about it.